The association between hemoglobin-to-red cell distribution width ratio and asthma and asthma exacerbations: a cross-sectional study - Chunling Kuang; Liuliu He; Qingfeng Zeng; Shasha Liao (BMC Pulmonary Medicine)
Abstract Background The hemoglobin-to-red cell distribution width ratio (HRR) is a newly identified inflammatory biomarker associated with various inflammatory diseases. Asthma is a major global health burden and an inflammatory airway disease significantly affected by inflammation. This study primarily aims to evaluate the relationship between HRR and asthma, as well as asthma-related outcomes, including stable asthma and asthma exacerbations in the past year. Methods Data from 2007 to 2023 were collected from the NHANES database. Multivariable logit and restricted cubic spline (RCS) analyses were conducted to elucidate the impact of HRR on asthma and its nonlinear relationship. Subgroup and interaction analyses were performed as part of the study’s sensitivity analysis. Results This study was based on an analysis of 13,343 individuals. According to logistic regression analysis, a higher HRR was associated with a lower likelihood of asthma (OR = 0.37, 95% CI: 0.23–0.6). Compared to the lowest group, the higher HRR group exhibited a 34% reduction in prevalence (OR = 0.66; 95% CI: 0.54–0.81, p < 0.01). According to RCS analysis, a linear relationship existed between HRR and asthmaprevalence. We further distinguished between stable asthma and acute exacerbations, and this association remained statistically significant. Conclusion This study observed an inverse association between HRR and asthma. Specifically, an increase in HRR was significantly associated with a lower prevalence of stable asthma and acute exacerbation, providing potential evidence for the use of HRR in evaluating asthma status.